1997
DOI: 10.1002/(sici)1520-6629(199709)25:5<421::aid-jcop4>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an Africentric worldview and demographic variables on drug knowledge, attitudes, and use among African American youth

Abstract: Alcohol, tobacco, and other drug use are major problems in the inner cities, especially for African American youth. Africentric values may be a protective factor for negative drug outcomes. The purpose of this study was to examine the influence of Africentric values, spirituality, and demographic variables on drug knowledge, attitudes, and use. Participants were 189 4th‐ and 5th‐graders attending public schools in Washington, DC, and Baltimore, Maryland. Measures of Africentric values (i.e., Collective Work/Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…African Americans who hold stronger Africentric world views are less likely to use alcohol (Brook & Pahl, 2005) and are more likely to hold negative views toward drugs, including alcohol (Belgrave et al, 2000, 1994; Belgrave, Townsend, Cherry, & Cunningham, 1997), than other African Americans. Likewise, Herd and Grube (1996) found that high levels of Black awareness and greater involvement in Black social networks was associated with reduced drinking and reduced heavy drinking among African Americans.…”
Section: Explaining Individual Differences In Risk Among African Amer...mentioning
confidence: 99%
See 1 more Smart Citation
“…African Americans who hold stronger Africentric world views are less likely to use alcohol (Brook & Pahl, 2005) and are more likely to hold negative views toward drugs, including alcohol (Belgrave et al, 2000, 1994; Belgrave, Townsend, Cherry, & Cunningham, 1997), than other African Americans. Likewise, Herd and Grube (1996) found that high levels of Black awareness and greater involvement in Black social networks was associated with reduced drinking and reduced heavy drinking among African Americans.…”
Section: Explaining Individual Differences In Risk Among African Amer...mentioning
confidence: 99%
“…Holding religious beliefs appears to provide additional protection, helping to identify those African Americans who are at reduced risk for alcohol or substance use (Brook & Pahl, 2005; Nasim et al, 2007; Stevens-Watkins & Rostosky, 2010; Zimmerman & Maton, 1992). For example, Belgrave et al (1997) found that among at-risk African American youth from an inner-city population, those with greater spiritual beliefs (i.e., attending religious services and discussing religion or spiritual topics within the home) reported less drug use than those with fewer spiritual beliefs. Moreover, religiosity has been shown to buffer the impact negative life events have on heavy drinking behaviors among youth in seventh through 10th grade (T.…”
Section: Explaining Individual Differences In Risk Among African Amer...mentioning
confidence: 99%
“…For example, researchers have found that positive alcohol expectancies are influenced by perceptions of peer use, whereas negative alcohol expectancies are not (Bekman, Goldman, Worley, & Anderson, 2011). Thus, it is possible that having a greater affinity toward one’s race/ethnicity and the values associated with that culture, such as spirituality and collective work/responsibility (i.e., the idea that people of the same ethnic group are responsible for one another and should work together to improve their family and community), can bolster negative outcome expectancies but may not influence positive outcome expectancies (Belgrave, Townsend, Cherry, & Cunningham, 1997). Accordingly, minorities tend to endorse similar rates of positive alcohol expectancies as Whites by early adolescence (Hipwell et al, 2005; Meier et al, 2007; Shih, Miles, Tucker, Zhou, & D’Amico, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that in a household with both parents, more supervision and monitoring of children can be provided, leading less drug use [24,25]. Niaz et al [26] also claimed that there were significant positive correlations between drug misuse and separated parents.…”
Section: Discussionmentioning
confidence: 99%